Pengaruh Peran Pengawas Minum Obat (PMO) terhadap Keberhasilan Pengobatan TB Paru di Puskesmas Pangkalan Kabupaten Karawang - Barkah, Asep; Suharjo, Ajo (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Pulmonary tuberculosis or pulmonary TB is still one of the deadliest infectious diseases in the world. Based on data from the Ministry of Health of the Republic of Indonesia (2022), the incidence of pulmonary TB in Indonesia is still quite high. Indonesia is the second country with the incidence of pulmonary TB after India. Treatment is the main way to eliminate pulmonary TB in Indonesia. However, several problems occur during TB treatment, resulting in many treatment failures. It is hoped that the role of PMO in the road map for eliminating pulmonary TB in Indonesia will be able to increase the success rate of pulmonary TB treatment. To determine the influence of the role of the PMO on the success of pulmonary TB treatment at the Pangkalan Community Health Center, Karawang Regency in 2025. This research is quantitative research with a retrospective analytical approach, namely evaluating events that have occurred previously and analyzing their influence on other variables. Respondents in the research were 77 respondents. Taking respondents using Consecutive Sampling technique. The research results showed that of the 77 respondents, the majority of PMOs played an active role, namely 74 (96.1%) PMOs, with 75 (97.4%) respondents being successful in treatment. The results of the analysis using the Chi-Square statistical test obtained a p value of 0.001 (p < 0.05), which means that there is an influence of the role of the PMO on the success of treatment of pulmonary TB sufferers at the Pangkalan Community Health Center. There is an influence on the role of the PMO on the success of pulmonary TB treatment at the Keywords: Drug Swallowing Monitor (PMO), Tuberculosis Treatment  ABSTRAK Tuberculosis paru atau TB paru masih menjadi salah satu penyakit menular paling mematikan di dunia.Berdasarkan Data Kementerian Kesehatan Republik Indonesia (2022) Kejadian TB paru di Indonesia masih cukup tinggi. Indonesia merupakan negara nomor dua dengan kejadian TB paru setelah India. Pengobatan merupakan jalan utama eliminasi TB paru di Indonesia. Namun beberapa masalah terjadi saat pengobatan TB sehingga banyak kegagalan pengobatan. Peran PMO dalam peta jalan eliminsasi TB paru di Indonesia sangat diharapkan mampu meningkatkan angka keberhasilan pengobatan TB Paru. Mengetahui pengaruh peran PMO terhadap keberhasilan pengobatan TB paru di puskesmas Pangkalan Kabupaten Karawang tahun 2025. penelitian ini adalah penelitian kuantitatif  dengan pendekatan analitik restrospektif yaitu melakukan evaluasi peristiwa yang telah terjadi sebelumnya dan menganalis pengaruhnya dengan variabel yang lain. Responden dalam penelitian sebanyak 77 responden. Pengambilan responden dengan teknik Consecutive Sampling. hasil penelitian menunjukkan dari 77 responden sebagian besar PMO berperan aktif sebanyak 74 (96,1%) PMO, dengan 75 (97,4%) keberhasilan responden dalam pengobatan. Hasil analisis analisis menggunakan uji statistik Chi-Square diperoleh nilai p value sebesar 0,001 (p < 0,05) yang berarti terdapat pengaruh peran PMO terhadap keberhasilan pengobatan penderita TB paru di Puskesmas Pangkalan. Ada pengaruh peran PMO terhadap keberhasilan pengobatan TB paru di puskesmas Pangkalan Kabupaten Karawang tahun 2025 Diharapkan penderita. Diharapkan pasien TB paru tetap menjaga pola hidup sehat  Kata Kunci: Pengawas Menelan Obat (PMO), Pengobatan Tuberkulosis